2017
DOI: 10.1139/apnm-2016-0459
|View full text |Cite
|
Sign up to set email alerts
|

Free-sugar, total-sugar, fibre, and micronutrient intake within elite youth British soccer players: a nutritional transition from schoolboy to fulltime soccer player

Abstract: It is recommended that soccer players consume a high carbohydrate (CHO) diet to augment performance. However, growing evidence suggests that there is a link between high freesugar (FS) intake (>5% total energy intake; TEI) and metabolic diseases. Furthermore, foods that are often high in sugar, such as processed foods, are typically lacking in nutrient quality.We therefore analysed total-and FS, dietary fibre and micronutrient intake of players from an English Premier League academy under(U) 18 (n=13); U15/16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In adults, the National Academy of Sciences Institute of Medicine recommends 20-35 g/d [101] and the UK Scientific Advisory Committee on Nutrition (SACN) recommends 30 g/d [102], whereas the Academy of Nutrition and Dietetics (AND, formerly American Dietetics Association) suggests an intake of 14 g of dietary fiber per 1000 kcal consumed daily (28-42 g/d and 22.4-33.6 g/d based on ADA-recommended calorie intakes for males (2000-3000 kcal/d based on age and activity levels) and females (1600-2400 kcal/d), respectively) [103]. Despite this, current dietary fiber consumption in omnivore runners is estimated at 27 g/d [104]; student-athlete fiber intake was reported at 20.9 g/d [105], and for squads of an elite youth soccer club, reported intake was at 25 g/d for U13/14 and U15/16, and 30 g/d for U18 [106]. As the tolerance to fiber is person-specific, a possible explanation of these modest levels of reduced intake in fiber-rich foods could be partly attributable to bloating, abdominal cramps, and increased flatulence experienced after fiber consumption [101].…”
Section: Microbial Production Of Scfas Via Different Dietary Fibersmentioning
confidence: 99%
“…In adults, the National Academy of Sciences Institute of Medicine recommends 20-35 g/d [101] and the UK Scientific Advisory Committee on Nutrition (SACN) recommends 30 g/d [102], whereas the Academy of Nutrition and Dietetics (AND, formerly American Dietetics Association) suggests an intake of 14 g of dietary fiber per 1000 kcal consumed daily (28-42 g/d and 22.4-33.6 g/d based on ADA-recommended calorie intakes for males (2000-3000 kcal/d based on age and activity levels) and females (1600-2400 kcal/d), respectively) [103]. Despite this, current dietary fiber consumption in omnivore runners is estimated at 27 g/d [104]; student-athlete fiber intake was reported at 20.9 g/d [105], and for squads of an elite youth soccer club, reported intake was at 25 g/d for U13/14 and U15/16, and 30 g/d for U18 [106]. As the tolerance to fiber is person-specific, a possible explanation of these modest levels of reduced intake in fiber-rich foods could be partly attributable to bloating, abdominal cramps, and increased flatulence experienced after fiber consumption [101].…”
Section: Microbial Production Of Scfas Via Different Dietary Fibersmentioning
confidence: 99%
“…Despite the high fiber content of the pulse-based diet, there were no negative effects on athletic performance. This is important, as young soccer players typically have a low intake of dietary fiber, and it is proposed that some might avoid fiber, for fear of gastrointestinal discomfort during training or games [10][11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…The high dietary fiber makes pulses a healthy food choice, because when pulses are consumed on a chronic basis (i.e., 8-16 weeks), they reduce harmful blood lipids [8,9], a major risk factor for cardiovascular disease. A number of studies evaluating diet in well-trained soccer players (males and females ranging in age from 16-22 years across studies) indicate that soccer players have relatively low intake of dietary fiber (i.e., about 55-67% of the recommended/reference intake) [10,11] and this may put them at risk of development of cardiovascular disease later in life [12]. It has been proposed that soccer players (mean age of 20 years) may avoid foods high in dietary fiber for fear it might cause gastrointestinal discomfort during training or games [13].…”
Section: Introductionmentioning
confidence: 99%
“…Protein intake followed the same pattern as senior players with a consistent intake throughout the week of 1.6 + 0.5 g·kg −1 , 1.4 + 0.6 g·kg −1 and 1.5 + 0.5 g·kg −1 for heavy training, moderate training and matches respectively; albeit these data illustrating an overall lower relative protein intake for academy players. Conclusions made from an investigation into the macronutrient intakes of an English Premiership academy [ 98 ], suggested that elite youth soccer players did not meet current CHO guidelines, although this conclusion may be difficult to define as their results are compared to senior guidelines as no such guidelines exist for academy players. Furthermore, there was an apparent difference between academy age specific squads, which was of interest but not understood, with their U18s only consuming 3.2 + 1.3 g·kg-1, much lower compared to the U13/14 (6.0 + 1.2 g·kg −1 ) and U15/16 (4.7 + 1.4 g·kg −1 ).…”
Section: Nutritional Intake and Soccermentioning
confidence: 99%